Ventricular pacemaker upgrade: experience, complications and recommendations. Issue 4 (1st April 1998) - Hildick-Smith, D J R; Lowe, M D; Newell, S A; Schofield, P M; Shapiro, L M; Stone, D L; Grace, A A; Petch, M C
Abstract : Objective: To assess outcomes of pacemaker upgrade from single chamber ventricular to dual chamber. Design —Retrospective analysis of patients undergoing the procedure. Setting —Specialist cardiothoracic unit. Patients —44 patients (15 female, 29 male), mean (SD) age at upgrade 68.2 (12.9) years. Interventions —Upgrade of single chamber ventricular to dual chamber pacemaker. Main outcome measures: Procedure duration and complications. Results —Principal indications for upgrade were pacemaker syndrome (17), "opportunistic"—that is, at elective generator replacement (8), heart failure (7), non-specific breathlessness/fatigue (7), and neurally mediated syncope (3). Mean (SD) upgrade procedure duration (82.9 (32.6) minutes) significantly exceeded mean VVI implantation duration (42.9 (13.3) minutes) and mean DDD implantation duration (56.6 (22.7) minutes) (both p < 0.01). Complications included pneumothorax (1), ventricular arrhythmia requiring cardioversion (2), protracted procedure (10), atrial lead repositioning within six weeks (8), haematoma evacuation (1), superficial infection (1), and admission to hospital with chest pain (1); 20 patients (45%) suffered one or more complications including four of the eight who underwent opportunistic upgrade. Conclusions: Pacemaker upgrade takes longer and has a higher complication rate than either single or dual chamber pacemaker implantation. This suggests that the procedure should be performed by an experienced operator, and should be undertaken only if a firm indication exists. Patients with atrial activity should not be offered single chamber ventricular systems in the belief that the unit can be upgraded later if necessary at minimal risk.